Pregunta
upstudy study bank question image url

nework Prove the identity. \[ \frac{1-\csc x}{\csc x+1}-\frac{\csc x+1}{1-\csc x}=4 \sec x \tan x \] To verify the identity, work each side separately until you obtain the same expression. Start with the left side. Choose the correct step and transform the expression according to the step chosen. 15 \( \frac{1-\csc x}{\csc x+1}-\frac{\csc x+1}{1-\csc x} \) \( =\square \)

Ask by Joseph Cummings. in the United States
Feb 26,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

\[ \frac{1 - \csc x}{\csc x + 1} - \frac{\csc x + 1}{1 - \csc x} = 4 \sec x \tan x \]

Solución

We wish to show that   (1 – csc x)/(csc x + 1) – (csc x + 1)/(1 – csc x) = 4 sec x tan x. One very neat choice for a first step is to combine the two fractions over a common denominator. That is, write   (1 – csc x)/(csc x + 1) – (csc x + 1)/(1 – csc x)     = { (1 – csc x)² – (csc x + 1)² }⁄[ (csc x + 1)(1 – csc x) ]. This is the correct step that “transforms the expression according to the step chosen” (i.e. choosing to combine the fractions by writing a common denominator). Let’s now quickly see how this step leads us to the answer. Step 1. Write as a single fraction:   (1 – csc x)/(csc x + 1) – (csc x + 1)/(1 – csc x)     = [ (1 – csc x)² – (csc x + 1)² ]⁄[ (csc x + 1)(1 – csc x) ]. Step 2. Notice that the numerator is a difference of two squares:   (1 – csc x)² – (csc x + 1)² = [(1 – csc x) – (csc x + 1)]·[(1 – csc x) + (csc x + 1)]. Compute each factor:   First factor: (1 – csc x) – (csc x + 1) = 1 – csc x – csc x – 1 = –2 csc x.   Second factor: (1 – csc x) + (csc x + 1) = 1 – csc x + csc x + 1 = 2. Thus, the numerator becomes:   (–2 csc x)(2) = –4 csc x. Step 3. Notice that the denominator simplifies by using the difference of two factors:   (csc x + 1)(1 – csc x) = 1 – csc² x. So the expression is now:   –4 csc x/(1 – csc² x). Step 4. Recall the Pythagorean identity for cosecant:   csc² x = 1 + cot² x  or equivalently 1 – csc² x = –cot² x. While this is one route, an even simpler method is to write everything in terms of sine and cosine. Using the definitions:   csc x = 1/sin x,  sec x = 1/cos x,  tan x = sin x/cos x, we can proceed by rewriting from the very beginning. Alternate route using sine and cosine:   Write LHS as   (1 – 1/sin x)/(1/sin x + 1) – (1/sin x + 1)/(1 – 1/sin x). Multiply numerator and denominator in each term by sin x:   = (sin x – 1)/(1 + sin x) – (1 + sin x)/(sin x – 1). Now observe that the two fractions are negatives of one another. Writing them over a common denominator:   = { (sin x – 1)² – (sin x + 1)² }⁄[ (sin x + 1)(sin x – 1) ]. The numerator becomes:   (sin x – 1)² – (sin x + 1)² = [sin²x – 2sin x + 1] – [sin²x + 2sin x + 1] = –4 sin x. And the denominator is   (sin x + 1)(sin x – 1) = sin²x – 1 = –(1 – sin²x) = –cos² x. Thus,   LHS = (–4 sin x)/(–cos² x) = 4 sin x/cos² x = 4 (sin x/cos x)(1/cos x) = 4 tan x sec x,  which is the desired right side. To summarize, one acceptable starting step is to rewrite the left side as   (1 – csc x)/(csc x + 1) – (csc x + 1)/(1 – csc x)     = [(1 – csc x)² – (csc x + 1)²]⁄[ (csc x + 1)(1 – csc x) ]. This is the step that transforms the expression into one that can then be simplified to obtain 4 sec x tan x.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Beyond the Answer

To begin simplifying the left side of the identity, we can combine the two fractions over a common denominator. The common denominator will be \((\csc x + 1)(1 - \csc x)\). So, we write: \[ \frac{(1 - \csc x)^2 - (\csc x + 1)^2}{(\csc x + 1)(1 - \csc x)} \] Now, let's simplify the numerator: \[ (1 - \csc x)^2 = 1 - 2\csc x + \csc^2 x \] \[ (\csc x + 1)^2 = \csc^2 x + 2\csc x + 1 \] Subtracting the second from the first gives: \[ (1 - 2\csc x + \csc^2 x) - (\csc^2 x + 2\csc x + 1) = -4\csc x \] Thus, the left side becomes: \[ \frac{-4 \csc x}{(\csc x + 1)(1 - \csc x)} = \frac{-4 \csc x}{-(\csc x^2 - 1)} = \frac{4 \csc x}{\csc^2 x - 1} \] Next, we recall that \(\csc^2 x - 1 = \cot^2 x\): \[ \frac{4 \csc x}{\cot^2 x} = 4 \csc x \cdot \tan^2 x = 4 \sec x \tan x \] Now we have shown that the left-hand side simplifies to the right-hand side of the identity, thus proving it. So, we write: \[ \frac{1-\csc x}{\csc x+1}-\frac{\csc x+1}{1-\csc x} = 4 \sec x \tan x \]

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad